Standardization in measurement: philosophical, historical and sociological issues - Schlaudt, Oliver; Huber, Lara (History and Philosophy of Technoscience, 2015)
The application of standard measurement is a cornerstone of modern science. In this collection of essays, standardization of procedure, units of measurement and the epistemology of standardization are addressed by specialists from sociology, history and the philosophy of science